Healing effect of a two‐herb recipe (NF3) on foot ulcers in Chinese patients with diabetes: A randomized double‐blind placebo‐controlled study2 (包含两种草本中药的配方（NF3）对中国糖尿病患者足部溃疡的治疗作用：一项随机双盲安慰剂对照的研究). (24th February 2014) - Ko, Chun Hay; Yi, Sui; Ozaki, Risa; Cochrane, Heidi; Chung, Harriet; Lau, Winnie; Koon, Chi Man; Hoi, Sandy W.H.; Lo, Winnie; Cheng, King Fai; Lau, Clara B.S.; Chan, Wai Yee; et al.
Abstract Background In the present study, we examined the effect of a two‐herb traditional Chinese medicine (NF3), comprised of Astragali Radix and Radix Rehmanniae, on the healing of diabetic foot ulcer and the possible molecular mechanisms involved. Methods This was a prospective randomized double‐blind placebo‐controlled study. Sixteen diabetic patients were randomized to receive either placebo or NF3 for 6 months. Ulcer healing and sensory changes were examined. Molecular studies included measurement of serum tumor necrosis factor (TNF)‐α and RNA microarray investigation. Results The daily rate of reduction in ulcer area was 3.55% in the NF3 group and 1.52% in the placebo group (P = 0.062). In the index limb, the number of negative tests for sensory neuropathy using monofilament was reduced from 27% to 7% in the NF3 group and from 37% to 35% in the placebo group (P < 0.001). In addition, NF3 significantly decreased serum TNF‐α levels (P = 0.034). Microarray studies revealed concerted changes following NF3 treatment in the expression of genes implicated in fibroblast regeneration, angiogenesis, and anti‐inflammation. Conclusions In this proof‐of‐concept study, 6‐month treatment with NF3 was associated with improved wound healing and sensation accompanied by concerted changes in gene expression.